2017
DOI: 10.3389/fnhum.2016.00655
|View full text |Cite
|
Sign up to set email alerts
|

Response Inhibition Is Facilitated by a Change to Red Over Green in the Stop Signal Paradigm

Abstract: Actions are informed by the complex interactions of response execution and inhibition networks. These networks integrate sensory information with internal states and behavioral goals to produce an appropriate action or to update an ongoing action. Recent investigations have shown that, behaviorally, attention is captured through a hierarchy of colors. These studies showed how the color hierarchy affected visual processing. To determine whether the color hierarchy can be extended to higher level executive funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 49 publications
5
40
0
Order By: Relevance
“…First, with retailers using the color red to signal a discounted price, consumers automatically perceive a promotion flyer using red prices to indicate that the store offers great savings (Puccinelli et al, 2013). Second, an almost ubiquitous use of red color to signal “stop” (e.g., traffic lights), has led consumers to associate red with inhibitory responses (Blizzard et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, with retailers using the color red to signal a discounted price, consumers automatically perceive a promotion flyer using red prices to indicate that the store offers great savings (Puccinelli et al, 2013). Second, an almost ubiquitous use of red color to signal “stop” (e.g., traffic lights), has led consumers to associate red with inhibitory responses (Blizzard et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Red color is used in traffic lights and other signage that signals “stop.” Studies on the effectiveness of stop signage find that compared to green stop signals, red signals are more effective (Blizzard, Fierro‐Rojas, & Fallah, 2017). Recent evidence of the red‐stop association has been provided by categorization studies in which words such as “stop” and “go” are presented in colors, such as red, green, and gray.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…This result provided the first electrophysiological evidence for hierarchical differences in the attentional selection of color. Even more recently, Blizzard et al ( 2017 ) demonstrated that red stop signals elicited faster response inhibition than green stop signals on a stop signal task, thus demonstrating hierarchical color selection involvement in higher stages of cognitive processing.…”
Section: Introductionmentioning
confidence: 99%
“…However, these few studies of the color hierarchy give conflicting accounts of the level in the visual processing hierarchy at which biased color selection occurs. For example, Lindsey et al ( 2010 ) provided evidence that the varying proportions of color signals from the L, M, and S color channels in the earliest stages of color processing explain the selection bias, whereas the results of Blizzard et al ( 2017 ) suggested that the biased selection of certain colors must take place at higher levels of cognitive processing associated with attentional deployment and executive function.…”
Section: Introductionmentioning
confidence: 99%
“…The mean time for selecting one color circle in the subsequent 190 trials of one experiment was about 470 ms ( Figure 1B). The difference in the speed of choosing a red or green circle for the purposes of our experiment was not a priority (Blizzard et al [20] found that the mean reaction time to a red stop signal was approximately 25 ms faster than that to a green stop signal).…”
Section: Methodsmentioning
confidence: 77%